Contemporary European practice in transcatheter aortic valve implantation: results from the 2022 European TAVI Pathway Registry - Rosseel, Liesbeth; Mylotte, Darren; Cosyns, Bernard; Vanhaverbeke, Maarten; Zweiker, David; Teles, Rui Campante; Angerås, Oskar; Neylon, Antoinette; Rudolph, Tanja Katharina; Wykrzykowska, Joanna J.; Patterson, Tiffany; Costa, Giulia; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: A steep rise in the use of transcatheter aortic valve implantation (TAVI) for the management of symptomatic severe aortic stenosis occurred. Minimalist TAVI procedures and streamlined patient pathways within experienced Heart Valve Centres are designed to overcome the challenges of ever-increasing procedural volume.Aims: The 2022 European TAVI Pathway Survey aims to describe contemporary TAVI practice across Europe.Methods: Between October and December 2022, TAVI operators from 32 European countries were invited to complete an online questionnaire regarding their current practice.Results: Responses were available from 147 TAVI centres in 26 countries. In 2021, the participating centres performed a total number of 27223 TAVI procedures, with a mean of 185 TAVI cases per centre (median 138;. Treatment strategies are usually (87%) discussed at a dedicated Heart Team meeting. Transfemoral TAVI is performed with local anaesthesia only (33%), with associated conscious sedation (60%), or under general anaesthesia in (7%). Primary vascular access is percutaneous transfemoral (99%) with secondary radial access in 52%. After uncomplicated TAVI, patients are transferred to a high-, medium-, or low-care unit in 28%, 52% and 20% of cases, respectively. Time to discharge is day 1 (12%), day 2 (31%), day 3 (29%), or day 4 or greater (28%).Conclusions: Reported adoption of minimalist TAVI techniques is common among European TAVI centres, but rates of next-day discharge remain low. This survey highlights the significant progress made in refining TAVI treatment and pathways in recent years and identifies possible areas for further improvement.